Chronic venou s disease - Liwień, Maciej (Przewodnik Lekarza/Guide for GPs, 2006)
Chronic venous disease (CVD) affects up to 40% of the world population. CVD can be caused by mechanical obstruction, venous valves insufficiency or both. Clinical manifestations of CVD are oedemas, varices, changes in skin pigmentation and venal ulcerations. The main diagnostic method is doppler ultrasound investigation. Conservative managment consists of avoiding risk factors, compression therapy and pharmacotherapy. Surgical treatment and modern techniques such as laser or thermoablation are performed. Early diagnosis and treatment of CVD is crucial for expecting a good prognosis in long term follow up.